2007
DOI: 10.1097/gim.0b013e3180318aaf
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the cystic fibrosis transmembrane conductance regulator gene in congenital absence of the vas deferens

Abstract: Purpose: Approximately 20% of patients with congenital absence of the vas deferens remain without two mutations identified. We applied a strategy of serial screening steps to 45 patients with congenital absence of the vas deferens and characterized cystic fibrosis transmembrane conductance regulator gene mutations in all cases.Methods: DNA samples of 45 patients with congenital absence of the vas deferens were screened by successive different molecular genetics approaches. Results: Initial screening for the 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 51 publications
2
16
1
1
Order By: Relevance
“…Thus CBAVD may represent an atypical incomplete (genital) form of CF [20]. The genetic link between CF and CBAVD has been confirmed by several studies that identified CFTR mutations in 80-100% of isolated CBAVD patients [24][25][26]. Clinical symptoms of CBAVD are characterized by azoospermia with low semen plasma volume (<1.5 ml) and low pH (<7.5), unilateral or bilateral non-palpable vas deferens, absence of the distal part of the epididymis and hypoplasia of the seminal vesicles [21].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Thus CBAVD may represent an atypical incomplete (genital) form of CF [20]. The genetic link between CF and CBAVD has been confirmed by several studies that identified CFTR mutations in 80-100% of isolated CBAVD patients [24][25][26]. Clinical symptoms of CBAVD are characterized by azoospermia with low semen plasma volume (<1.5 ml) and low pH (<7.5), unilateral or bilateral non-palpable vas deferens, absence of the distal part of the epididymis and hypoplasia of the seminal vesicles [21].…”
Section: Introductionmentioning
confidence: 71%
“…Mutations in CFTR were found to have an impact on human reproduction and consequently about 98% of male CF patients are infertile due to obstructive azoospermia, which is associated with congenital absence of the vas deferens (CBAVD; MIM 277180) [17,18]. Mutations in CFTR gene have also been identified in patients with isolated CBAVD and in the absence of other clinical CF symptoms [19][20][21][22][23][24]. Thus CBAVD may represent an atypical incomplete (genital) form of CF [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CFTR mutations may cause CBAVD in the absence of CF. Patients with CBAVD but without CF, present one severe CFTR mutation in one allele and one mild CFTR mutation in the other, or two mild CFTR mutations in the two alleles [Grangeia et al 2004;Grangeia et al 2007]. Functional sperm are produced, since testicular sperm can be recovered for intracytoplasmic sperm injection (ICSI) treatment cycles by testicular sperm extraction, with very satisfactory results [Larriba et al 1998;Wong et al 1998;Sousa et al 2002;Grangeia et al 2004;Grangeia et al 2007].…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition to CF, CFTR variants are also responsible for other diseases, usually monosymptomatic and classified as CFTR-related disorders (RD). 16 Many of these patients may carry a CF-pathogenic variant on one allele and a likely pathogenic variant on the other allele, or even in both alleles.…”
Section: Introductionmentioning
confidence: 99%